On exact proper time Wilsonian RG flows - Bonanno, Alfio; Lippoldt, Stefan; Percacci, Roberto; Vacca, Gian Paolo (The European physical journal. C, Particles and fields, 2020)
We discuss the possibility to define exact RG equations for a UV regulated Wilsonian action based on a proper time (PT) regulator function. We start from a functional mapping which shows how each particular flow equation (and RG scheme) is associated to infinitely many scale dependent field redefinitions, which are related to specific coarse-graining procedures. On specializing to a sub-family of one parameter PT regulators we briefly analyze few results for the Ising Universality class in three dimensions, obtained within a second order truncation in the derivative expansion of the Wilsonian action.